Role of ultrasound measuring position and ventilation pressure in determining correct tube size in children - Schramm, Christoph; Eisleben, Luzie Sarah; Keßler, Jens; Jensen, Katrin; Plaschke, Konstanze (Pediatric anesthesia, 2017)
Background: Ultrasound measurements of the airway are useful for determining correctly sized, uncuffed endotracheal tubes in children. Aims: The primary objective of this study was to evaluate the influence of ventilation pressure on the sonographically measured tracheal diameter at different levels. Methods: A total of 100 patients (under 7 years) were enrolled in this study. Six sonographic measurements of minimal transverse diameters at 3 locations (vocal chords, cricoid cartilage, and proximal trachea) and at 2 different ventilation pressures (0 and 15 mbar) were performed before the intubation procedure. The intubating anesthesiologists were blinded to the results of the ultrasound measurements. The rate of agreement of the outer diameter of the correctly sized endotracheal tube (reference) with the 6 sonographic diameters was determined. In addition, the correct tube sizes were compared with the results of traditional prediction methods (Penlington's and Cole's formula in children ≥1 year and a decision table in children <1 year). Results Best rate of agreement resulted from cricoid cartilage (70% and 83% at 0 and 15 mbar). Conclusion: The airway level selected for ultrasound and airway pressure during measurement determines the rate of agreement between the measurement result and correct ETT size.
Gesehen am 20.08.2018
First published: 24 October 2017